A new generation of high-affinity humanized PEGylated Fab´´ fragment anti-tumor necrosis factor-αα monoclonal antibodies. Issue 4 (July 2006) - Weir, Neil; Athwal, Dee; Brown, Derek; Foulkes, Roly; Kollias, George; Nesbitt, Andrew; Popplewell, Andy; Spitali, Mari; Stephens, Sue
Advances in immunotherapy through the development of chimeric, humanized and fully human monoclonal antibodies have improved treatment and reduced immunogenicity. These strategies produced biological anti-tumor necrosis factor-αα therapies for inflammatory conditions, including Crohn´´s disease and rheumatoid arthritis. Antibody fragments, including antigen-binding fragments, are a further advance in antibody-based therapy. Certolizumab pegol is a PEGylated humanized antigen-binding fragment of an anti-tumor necrosis factor-αα monoclonal antibody. PEGylation extends the half-life and is compatible with subcutaneous administration, while humanization may reduce immunogenicity. Large-scale antigen binding fragment production is possible via microbial fermentation. This review details how the monoclonal antibody was generated, selected and humanized from the original parent murine antibody, and summarizes the pharmacological characteristics, efficacy and safety data that distinguish it from the full monoclonal antibody anti-tumor necrosis factors that are currently available.